PERANCANGAN VIDEO KAMPANYE “AYO KE STADION” MENDUKUNG SEMEN PADANG FC - FAZRI RIDWAN LIPALMA, San Ahdi, S.Sn., M.Ds., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Football clubs will never be separated from their supporters, because the supporters are the life of the team. Semen Padang Fc has two groups of supporters, namely The Kmer's and Spartack's, by the end of 2017, Semen Padang Fc is experiencing a downturn, Semen Padang FC must be relegated to the Indonesian two-league caste, this makes the enthusiasm of the people decline to come directly to the stadium supporting Semen Padang FC.To reciprocate the Society's enthusiasm a Campaign is required, the Campaign is an activity to influence the community by planning activities to achieve a particular goal. The purpose of this campaign video design is to invite people to come back to the stadium directly support the local club of West Sumatra, Semen Padang Fc.The design method of the authors use qualitative descriptive that is interpreting and related data related to the situation that is happening within the community. In addition the authors use the 5W + 1H method, used to problem solving in the background and find solutions of the problem.The design of the campaign